1994
DOI: 10.1002/app.1994.070520608
|View full text |Cite
|
Sign up to set email alerts
|

Chemical structure and physical properties of antheraea assama silk

Abstract: SYNOPSISThis work deals with the chemical composition, physical structure, and thermal behavior of Antheraea assama silk fibers. The amino acid composition is characterized by the high content of alanine, glycine, and serine. Among the amino acid residues with polar side chains, aspartic acid, arginine, and tyrosine prevail. The birefringence and isotropic refractive index values are 0.030 and 1.557, respectively. The stress-strain curve shows a yield point at 5% elongation, followed by a region of gradual ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 20 publications
7
58
0
Order By: Relevance
“…The proportion of alanine is about 34% in tasar, 36% in eri, and 35% in muga. This value is consistent but is lower than that reported by Freddi et al, 11 particularly for muga (ϳ 44%). On the other hand, the glycine content in these varieties is about 27-29%, which is lower than that found in the mulberry varieties (ϳ 43%).…”
Section: Amino Acid Composition and Analysissupporting
confidence: 52%
See 1 more Smart Citation
“…The proportion of alanine is about 34% in tasar, 36% in eri, and 35% in muga. This value is consistent but is lower than that reported by Freddi et al, 11 particularly for muga (ϳ 44%). On the other hand, the glycine content in these varieties is about 27-29%, which is lower than that found in the mulberry varieties (ϳ 43%).…”
Section: Amino Acid Composition and Analysissupporting
confidence: 52%
“…Muga was shown to have the least, with 67.77%. In a study on chemical composition and physical properties of Antheraea assama silk, Freddi et al 11 reported a high alanine content of 42.62% and very low arginine content (2.83%), although cystine (0.34%) was present and the other sulfur-containing amino acid, methionine, was not detected in their analysis.…”
Section: Introductionmentioning
confidence: 92%
“…The functional adaptations of these crystals and the colour of cocoons range from camouflage to heat absorption or light transmission [12]. Other wild silk cocoons, such as A. assama, also showed the presence of calcium oxalate crystal deposits on their surface [13]. The difference in the size and shape of the crystals suggests the role they might have on influencing the texture of the cocoon surface.…”
Section: Discussionmentioning
confidence: 98%
“…The amino acid sequence in the crystalline region of BSF and TSF was considered to be (GAGAGS)n (G: glycine, A: alanine, S: serine) and -(ala)-, respectively. 44,45 So the TSF molecular chains would form a more compact crystalline structure than BSF, resulting in higher thermal decomposition peaks (Fig. 5).…”
Section: View Article Onlinementioning
confidence: 99%